Livelihoods Strategies to Create Happiness of Elderly with Disabilities in Khon Kaen Smart City - Narongchai, Wanichcha; Phutthanathanapa, Chittima; Prasertrungruang, Montree (Journal of Humanities and Social Sciences Thonburi University, 2022)
This article aims to investigate the livelihood strategies to create happiness in the elderly with disabilities [EWD] in Khon Kaen Smart City, which uses a mixed methods research methodology. First, the qualitative data targeting various kinds of EWD and their stakeholders in Khon Kaen Smart City 40 people was adopted from an in-depth interview, and group interviews. Second, the quantitative collected data by a questionnaire with a sample of 384 people. The data was presented by content analysis together with the descriptive statistical analysis. The results found that the livelihoods of the EWD in Khon Kaen Smart City were mostly at moderate and high levels, accounting for 61.2% and 22.4%, respectively. The highest average score was an aspect of survivability, followed by aspects of alternative, sustainability, struggling, and solution finding, respectively. In addition, the EWD showed their livelihoods strategies for happiness as follows: self-made happiness, happy creations, happy family, and happy community and society. So, the EWD receiving the welfare of the Khon Kaen Smart City for promoting the livelihood of the elderly with disabilities happiness even more.